Achieving Sustainable Mobility : Why Policy-Makers Should Pursue the Four Goals at the Same Time - Morales Sarriera, Javier; Fulton, Lewis (World Bank, Washington, DC, 2018)
The Global Mobility Report frames the transport agenda around four global goals: universal access, efficiency, safety and green. Unless those four goals are pursued simultaneously, mobility will not be sustainable for current and future generations. For example, policy decisions must not prioritize universal access interventions without considering the implications they may have on efficiency, safety, and green. Deviating from any of the goals will compromise the achievement of sustainable mobility. At stake is the fact that none of these goals are independent, but they are all interconnected. In many cases, there are synergies among pairs of goals, or even across all four. Synergies occur when projects and policies help achieve more than one goal at a time. Butin other cases, advancing the agenda on one goal may hinder another. Therefore, synergies shouldbe captured and apparent trade-offs should be managed. By acknowledging these interconnections and managing them appropriately, mobility will be able to generate more benefits for society, strengthening its role as a driver of social inclusion and economic competitiveness, with the least impact on safety and the environment. This note provides examples of the synergies and trade-offs a policy-maker should consider and manage.